The elderly’s social behavior development towards Thai society at the age of 4.0 of Ban Kong Sao, Nabon Sub-district, Nabon District, Nakhon Si Thammarat Province - Saengae Sanjun, Kittiporn; Nillakan, Lunjakon; Lertgri, Punya; Thaicharoen, Wichian (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to study the context and condition of the elderly’s social behavior development towards Thai society in the age of 4.0 and to study the learning process and social behavior development of the elderly towards Thai society in the age of 4.0 in Ban Kong Sao, Nabon Sub-district, Nabon District, Nakhon Si Thammarat Province. It is qualitative research and research & development (R&D) by studying information from documentary research and fieldwork through surveys, observations, in-depth interviews, and focus groups. The study found that context and condition of the elderly’s social behavior development at Ban Kong Sao community, where it is flatland, soil contains fertile, and doing rubber plantations and fruit orchards mainly. People in the community have kinship and interact closely with each other, being a society based on custom. The learning and behavior development process caused by push factors such as having physical health problems and living alone is why they need to get into the online society to develop themselves towards society in the age of 4.0. It has to be learned how to use a smartphone to get online by themselves. The pull factor is people who are members of the elderly group, causing them to participate in activities and live happily in society, creating the power to develop oneself into society at the age of 4.0 that helps resolve health problems, both physical and mental, of the elderly.